IL-1β-Mediated Activation of Adipose-Derived Mesenchymal Stromal Cells Results in PMN Reallocation and Enhanced Phagocytosis: A Possible Mechanism for the Reduction of Osteoarthritis Pathology - van Dalen, Stephanie C. M.; Blom, Arjen B.; Walgreen, Birgitte; Slöetjes, Annet W.; Helsen, Monique M. A.; Geven, Edwin J. W.; ter Huurne, Menno; Vogl, Thomas; Roth, Johannes; van de Loo, Fons A. J.; Koenders, Marije I.; Casteilla, Louis; et al. (Frontiers in Immunology, 2019)
Background: Injection of adipose-derived mesenchymal stromal cells (ASCs) into murine knee joints after induction of inflammatory collagenase-induced osteoarthritis (CiOA) reduces development of joint pathology. This protection is only achieved when ASCs are applied in early CiOA, which is characterized by synovitis and high S100A8/A9 and IL-1β levels, suggesting that inflammation is a prerequisite for the protective effect of ASCs. Our objective was to gain more insight into the interplay between synovitis and ASC-mediated amelioration of CiOA pathology. Methods: CiOA was induced by intra-articular collagenase injection. Knee joint sections were stained with haematoxylin/eosin and immunolocalization of polymorphonuclear cells (PMNs) and ASCs was performed using antibodies for NIMP-R14 and CD271, respectively. Chemokine expression induced by IL-1β or S100A8/A9 was assessed with qPCR and Luminex. ASC-PMN co-cultures were analyzed microscopically and with Luminex for inflammatory mediators. Migration of PMNs through transwell membranes towards conditioned medium of non-stimulated ASCs (ASCNS-CM) or IL-1β-stimulated ASCs (ASCIL-1β-CM) was examined using flow cytometry. Phagocytic capacity of PMNs was measured with labeled zymosan particles. Results: Intra-articular saline injection on day 7 of CiOA increased synovitis after 6 hours, characterized by PMNs scattered throughout the joint cavity and the synovium. ASC injection resulted in comparable numbers of PMNs which clustered around ASCs in close interaction with the synovial lining. IL-1β-stimulation of ASCs in vitro strongly increased expression of PMN-attracting chemokines CXCL5, CXCL7, and KC, whereas S100A8/A9-stimulation did not. In agreement, the number of clustered PMNs per ASC was significantly increased after 6 hours of co-culturing with IL-1β-stimulated ASCs. Also migration of PMNs towards ASCIL-1β-CM was significantly enhanced (287%) when compared to ASCNS-CM. Interestingly, association of PMNs with ASCs significantly diminished KC protein release by ASCs (69% lower after 24h), accompanied by reduced release of S100A8/A9 protein by the PMNs. Moreover, phagocytic capacity of PMNs was strongly enhanced after priming with ASCIL-1β-CM. Conclusions: Local application of ASCs in inflamed CiOA knee joints results in clustering of attracted PMNs with ASCs in the synovium, which is likely mediated by IL-1β-induced up-regulation of chemokine release by ASCs. This results in enhanced phagocytic capacity of PMNs, enabling the clearance of debris to attenuate synovitis.